PENGARUH HARGA, KUALITAS PELAYANAN, KEPERCAYAAN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIANPONSEL - Nur Fachodhi, 09.05.51.0037 (Students Journal of Economic and Management, 2013)
Research Entitled Effect Of Price, Quality Service, Trust And Campaign Against Mobile Purchase Decision (Studies In Semarang Trade Center (Sctc) Matahari Plaza Semarang Simpang Lima Thisisa Study To Determineand Analyze Whet HerÂ The Variable Price, Quality Of Service, Trust, And The Promotion Of Semarang Celular Trade Center (Sctc) Matahari Plaza Semarang Simpang Lima Significantly Influence Customers Purchasing Decisions Semarang Celular Trade Center (Sctc). Authors There For Take The Title